2022
DOI: 10.3390/antibiotics11040495
|View full text |Cite
|
Sign up to set email alerts
|

Combating Bacterial Biofilm Formation in Urinary Catheter by Green Silver Nanoparticle

Abstract: Urinary catheters are commonly associated with urinary tract infections. This study aims to inhibit bacterial colonisation and biofilm of urinary tract catheters. Silicon catheter pieces were varnished with green silver nanoparticles (AgNPs) using Pistacia lentiscus mastic to prevent bacterial colonisation. Pomegranate rind extract was used to synthesize AgNPs. AgNPs were characterized by UV-Vis spectroscopy, X-ray crystallography, and transmission electron microscopy (TEM). Results obtained revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…8 Within recent years, there have been breakthroughs in materials science and sexual health to target these risks. Commercially available urinary catheters have been modified with polydopamine, 9 metal nanoparticles, 10,11 and S-nitrosothiols, 12 creating antimicrobial interfaces to decrease the potential of UTI onset. Additionally, sexual health professionals are beginning to understand the correlation between sexual activity and condom use with UTI development in women.…”
mentioning
confidence: 99%
“…8 Within recent years, there have been breakthroughs in materials science and sexual health to target these risks. Commercially available urinary catheters have been modified with polydopamine, 9 metal nanoparticles, 10,11 and S-nitrosothiols, 12 creating antimicrobial interfaces to decrease the potential of UTI onset. Additionally, sexual health professionals are beginning to understand the correlation between sexual activity and condom use with UTI development in women.…”
mentioning
confidence: 99%
“…To assess the antibacterial efficacy of the duloxetine-coated silicone catheter against S. aureus , an in vitro bladder model was employed, following the methodology described in a previous study. 26 Concisely, small pieces of the silicone catheter tube were immersed in a duloxetine solution (37.5 mg/mL) for 1 h. The air-dried, drug-coated pieces were then placed onto sterile Mueller–Hinton agar (MHA) plates that had been swabbed with an overnight S. aureus culture, and the plates were subsequently incubated. The presence of an inhibition zone around the well indicated the antibacterial activity of the drug-coated catheter tube.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…and proved the potent anti-biofilm activity against a wide range of bacteria, including Escherichia coli , P. aeruginosa , Staphylococcus epidermidis , and S. aureus. Goda et al (2022) synthesized AgNPs using pomegranate extract and showed their potent anti-biofilm activity against a range of Gram-positive ( S. epidermidis and S. aureus ) and Gram-negative bacteria ( E. coli , K. pneumoniae , P. aeruginosa , and P. mirabilis ) . The AgNPs were immobilized on catheters and showed high activity against Gram-positive bacteria as compared to Gram-negative bacteria.…”
Section: Nanotechnological Approaches For Biofilm Controlmentioning
confidence: 99%